2021
DOI: 10.21203/rs.3.rs-570604/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Rectal Temperature of Goats Based on Surface Temperature

Abstract: Infrared thermography (IR) is a non-invasive tool with potential to indicate changes in the animal's thermal conditions in response to the thermally stressful environment. The objective of this study was to evaluate the application of IR to estimate the rectal temperature of crossbred goats of the Boer breed. Six male crossbred goats of the Boer breed were distributed in a completely randomized design and submitted to temperatures of 26, 30 and 34 °C and 68% relative humidity. Rectal temperature (RT) and therm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In most cases, animals exposed to heat stress tend to have an elevated core body temperature, breathing rate, heart rate, changing endocrine function, sweating, and metabolic activity [7,16,47,48]. According to Marques [49], an increase in the goats' core temperature from 38.0 0 C to 39.0 0 C indicates that the animal has been kept at a hot ambient temperature for more than six hours. Another study by Al-Dawood [50] reported that an increase in rectal temperature above 44 0 C indicates that the animal has been exposed to higher temperatures.…”
Section: Behavioral and Physiological Mechanisms Of Thermoregula-tionmentioning
confidence: 99%
“…In most cases, animals exposed to heat stress tend to have an elevated core body temperature, breathing rate, heart rate, changing endocrine function, sweating, and metabolic activity [7,16,47,48]. According to Marques [49], an increase in the goats' core temperature from 38.0 0 C to 39.0 0 C indicates that the animal has been kept at a hot ambient temperature for more than six hours. Another study by Al-Dawood [50] reported that an increase in rectal temperature above 44 0 C indicates that the animal has been exposed to higher temperatures.…”
Section: Behavioral and Physiological Mechanisms Of Thermoregula-tionmentioning
confidence: 99%